An industry perspective on Canadian patients' involvement in Medical Tourism: implications for public health - Snyder Jeremy; Adams Krystyna; Crooks Valorie A; Johnston Rory; Kingsbury Paul (BMC, 2011)
Abstract Background The medical tourism industry, which assists patients with accessing non-emergency medical care abroad, has grown rapidly in recent years. A lack of reliable data about medical tourism makes it difficult to create policy, health system, and public health responses to address the associated risks and shortcomings, such as spread of infectious diseases, associated with this industry. This article addresses this knowledge gap by analyzing interviews conducted with Canadian medical tourism facilitators in order to understand Canadian patients' involvement in medical tourism and the implications of this involvement for public health. Methods Semi-structured phone interviews were conducted with 12 medical facilitators from 10 companies in 2010. An exhaustive recruitment strategy was used to identify interviewees. Questions focused on business dimensions, information exchange, medical tourists' decision-making, and facilitators' roles in medical tourism. Thematic analysis was undertaken following data collection. Results Facilitators helped their Canadian clients travel to 11 different countries. Estimates of the number of clients sent abroad annually varied due to demand factors. Facilitators commonly worked with medical tourists aged between 40 and 60 from a variety of socio-economic backgrounds who faced a number of potential barriers including affordability, fear of the unfamiliar, and lack of confidence. Medical tourists who chose not to use facilitators' services were thought to be interested in saving money or have cultural/familial connections to the destination country. Canadian doctors were commonly identified as barriers to securing clients. Conclusions No effective Canadian public health response to medical tourism can treat medical tourists as a unified group with similar motivations for engaging in medical tourism and choosing similar mechanisms for doing so. This situation may be echoed in other countries with patients seeking care abroad. Therefore, a call for a comprehensive public health response to medical tourism and its effects should be coupled with a clear understanding that medical tourism is a highly diverse practice. This response must also acknowledge facilitators as important stakeholders in medical tourism.